Taxonomic Morphological Study of the Stink Bug Bagrada hilaris (Burmeister, 1835) (Hemiptera: Pentatomidae) in Some Regions of Central - Hamid, Ahmed Waleed; Sabr, Ahmed Jameel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
We conducted a taxonomic and phenotypic study on Bagrada hilaris, collected from various regions in central Iraq such as Baghdad, Diyala, and Babel governorates, between the end of May and October 2022. The study showed that the third segment of the antennae is the longest of all segments, and the head contains a pair of simple brown eyes. The rostrum extends to the end of the hind leg coxa, and each abdominal ring contains a pair of spiracles. The tarsus consists of three segments and bears a pair of claws. The phallus and paramere, representing male genitalia, consist of two parts: a medium-thick basal part known as the stem and a broad apical part known as the blade. The blade consists of two protrusions of unequal length. The genitalia of the female are attached to the eighth and ninth abdominal rings. The dorsal tergates of these rings are folded ventrally on each side to make the ventral part of the side of the dorsal plates